The Effect of Pisa Score, Tertiary Education, and Wages on Labor Productivity in Indonesia - Annisya Dwi Hapsari; Fadjar, Nurman Setiawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Indonesia is predicted to face a demographic bonus, which is expected to drive an increase in labor productivity. Human capital and wages can serve as key factors to increase labor productivity in Indonesia. This study grounded in the theories of Total Factor Productivity (TFP), Becker’s Human Capital, Efficiency Wages, and Marginal Productivity, aiming to analyze the impact of cognitive knowledge through PISA scores, tertiary education attainment, and average wages on labor productivity in Indonesia. The findings reveal that human capital has a significant influence on labor productivity, while wages not show a significant impact when combined with human capital.